Ultraviolet exposure from indoor tanning devices as a potential source of health risks: Basic knowledge of the proper use of these devices for practical users, physicians and solarium staff - Jolanta Malinowska-Borowska; Elżbieta Janosik (Nofer Institute of Occupational Medicine, 2017)
Bearing in mind the adverse health effects of exposure to ultraviolet (UV) radiation in solarium, especially the risk of carcinogenesis, there is a need to adopt legal regulations by relevant Polish authorities. They should set out the principles for indoor tanning studios operation, supervision and service of the technical parameters of tanning devices and training programs to provide the staff with professional knowledge and other aspects of safety in these facilities. The mechanism of the harmful effects of ultraviolet radiation on the human body, scale of overexposure, resulting from excessive sunbathing are described. Methods for estimating UV exposure and possible actions aimed at reducing the overexposure and preventing from cancer development caused by UV are also presented in this paper. Med Pr 2017;68(5):653-665